Effect of Multimodal Intervention on Cancer-Related Fatigue and Quality of Life among Patients Undergoing Cancer Treatment—Pilot Study (Part 1) - Shambhavi, Shambhavi; Lobo, Diana (Journal of Health and Allied Sciences NU, 2023)
Background Cancer-related fatigue (CRF) is the most common and devastating problem in cancer patients even after successful treatment. CRF has a severe impact on daily activities, social relationships, reintegration, and overall quality of life (QOL).Objective This study was done to evaluate the effect of multimodal intervention (MMI) on CRF and QOL among cancer patients undergoing cancer treatment.Materials and Methods One group before-and-after study (pre-experimental design) was conducted among cancer patients undergoing cancer treatment who met inclusion criteria and were selected using a purposive sampling technique, in selected hospitals. MMI consisted of exercise program, acupressure, and home care management guide. Pre-test CRF and QOL were assessed on first day using a FACIT-F scale (Functional Assessment of Chronic Illness Therapy: Fatigue) and Functional Assessment of Cancer Therapy: Fatigue (FACT-G) Version 4, respectively. Post- test for CRF was further determined after 7 days, 21 days, and 3months and QOL was determined after 21 days and 3 months.Statistical Analysis Demographic and clinical characteristics of the participants are presented as frequency and percentage. Comparison of pre- test and post-test means of CRF and QOL is done by repeated measures analysis of variance (ANOVA). Correlation between fatigue and QOL of cancer patients was found by using Pearson correlation test.Results The mean pre-test fatigue score of the cancer patients (pre-test mean= 25.21) was lower than their mean post-test fatigue scores (post-test 1 =25.83, post-test 2 = 28.28, and post-test 3 = 34.72). There was a significant difference in CRF and QOL scores between before and after the MMI. In the repeated measures ANOVA, p-value is less than 0.05 (level of significance p < 0.05).Conclusion Regardless of mechanism of occurrence of fatigue, most patients living with cancer suffer with persistent CRF. Yet it is often not assessed, has limited treatment options, there is a need to assess the state of fatigue in cancer patients. They do need intervention to reduce the fatigue and to improve the QOL. Nonpharmacological therapies are the best strategies to manage the fatigue among cancer patients without any safety issue.
Keywords: acupressure; cancer-related fatigue; exercise program; home care; nonpharmacological therapies; quality of life